2020
DOI: 10.3389/fneur.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity Patterns of Subthalamic Stimulation Influence Pain Outcomes in Parkinson's Disease

Abstract: Background: Pain is highly prevalent in Parkinson's disease and is associated with significant reduction in health-related quality of life. Subthalamic deep brain stimulation can produce significant pain relief in a subset of patients after surgery. However, the mechanism by which deep brain stimulation modulates sensory function in Parkinson's disease remains uncertain.Objective: To describe the motor and pain outcomes of deep brain stimulation applied to a series of patients with Parkinson's disease and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
0
18
0
6
Order By: Relevance
“…Therefore, we suggest that the results are due to the following two aspects: (i) STN-DBS does not change the pain network in a short time. It requires long-term stimulation to reshape the pain network and gradually increase the pain threshold of a patient (Pautrat et al, 2018 ; Cury et al, 2020 ; Dogru Huzmeli et al, 2020 ). (ii) Usually, the network of pain in patients includes inner pathways related to emotions and outer pathways related to nociceptive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the results are due to the following two aspects: (i) STN-DBS does not change the pain network in a short time. It requires long-term stimulation to reshape the pain network and gradually increase the pain threshold of a patient (Pautrat et al, 2018 ; Cury et al, 2020 ; Dogru Huzmeli et al, 2020 ). (ii) Usually, the network of pain in patients includes inner pathways related to emotions and outer pathways related to nociceptive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…While most investigations of the origins of PD movement disorder (MD) focus exclusively on the basal ganglia (BG) (commonly the pallidal-STN loop), other circuitry, notably the thalamus, corticothalamic loop, and the BG-cortico-thalamic loop, may contribute to pathological BG processing and therefore are all open to test by modelling (see Figure 1 in van Albada et al [8]). Likewise, it should not be ignored that DBS for non-MD symptoms such as pain may be valuable sources for DBS PD for MD model calibration and validation [51].…”
Section: Other Relevant Pathwaysmentioning
confidence: 99%
“…This work supports the orthodromic theory of DBS PD that, with SNc dopaminergic neuronal loss, GPe inhibition of STN weakens, producing elevated synchrony, in turn producing PD MD symptoms by blocking normal BG-MC signaling. DBS to dorsolateral STN or GPi reduces BG-thalamo-cortical synchrony and synchrony within the cortical motor areas, as indicated by beta-band power, thus removing the 'information block', restoring normal BG-MC signaling via thalamo-cortical projections [20,21,51]. If further studies reinforce this conclusion, it is a major clarification of DBS PD MoA and would help to focus modelers' efforts, beginning with reproducing the results of Johnson et al and incorporating the required parameters as a calibration of models including the motor cortex.…”
Section: Current Theory Of Dbs Pd Mechanism Of Action At the Circuit ...mentioning
confidence: 99%
“…Growing evidence has showed that depending on the symptoms, connectomic DBS can act on different circuits in the brain. In this way, the neuromodulation surgery can affect both motor and non-motor functions (Table 2) [23,45,61,[72][73][74][75][76][77][78][79].…”
Section: Connectomic Dbs In Pdmentioning
confidence: 99%